Diaporthe betae sp. nov., a new species associating with sugar beet root rot in Heilongjiang Province, China - Shao, Hongtao; Ma, Chunquan; Yu, Bing; Chen, Sixue; Li, Haiying (Frontiers in Microbiology, 2025)
IntroductionSugar beet (Beta vulgaris L.) is an economically important crop grown worldwide, but its production is threatened by root rot diseases caused by soil-borne fungi. This study aimed to identify and characterize a new pathogen causing root rot in sugar beet in Heilongjiang Province, China.MethodsDuring 2019 and 2023, isolates were obtained from infected sugar beet roots showing symptoms of red-brown or black lesions and tissue necrosis. The pathogenicity of the causal organism was confirmed by Koch’s postulates. The isolates were characterized based on morphological features and multilocus phylogenetic analyses. To evaluate potential control measures for this new pathogen in field conditions, the fungicides pyraclostrobin, boscalid, and fluconazole were tested for their efficacy in inhibiting the growth of this new pathogen in vitro.ResultsThe newly discovered pathogen was found to differ from previously described taxa in conidial morphology, molecular features, and disease index. Thus, the pathogen was determined to be a new species, which we called Diaporthe betae sp. nov. All three fungicides demonstrated significant inhibitory effects, with fluconazole showing the strongest activity and pyraclostrobin the second-highest efficacy.DiscussionThe discovery of this new pathogenic fungus will help researchers elucidate the pathogenesis of sugar beet root rot and provide a theoretical basis for performing targeted monitoring, preventing diseases and implementing control measures.